Right Dorso-Caudal Flank Laparohysterotomy to Manage Prolonged Macerated Fetal Retention in a Cow - Ahuja, Ankit; Kumar, Pravesh; Sood, Pankaj; Sharma , Akshay; Sharma, Amit (The Indian Journal of Animal Reproduction, 2025)
A six-year-old pluriparous cow was presented with a history of retained macerated fetus for 99 days. Due to the pelvic location of the uterus, surgical exteriorisation was done through right dorso-caudal flank. Bunch of fetal bones, with 25 ml of purulent exudate, from right uterine horn and two tiny bone fragments at the caudal region of left uterine horn was removed. Follow-up revealed the cow exhibited overt estrus fourteen days post-surgery.